The resurrection of Durga: Indira Gandhi's spectacular politics in the 1980s - Sawkar, S (2018)
The cult of personality around Prime Minister Indira Gandhi has traditionally been explained with reference to her role in the Bangladesh War, the Emergency, and Operation Blue Star. Moreover, historiographical narratives woven around these episodes largely portray her as a champion of ‘socialism’ and the poor. Going beyond these characterisations, this thesis is organised around four ‘state spectacles’ that captured Indian middle class imagination in the early 1980s – the Asian Games in New Delhi (1982), the launch of the Maruti-Suzuki ‘family car’ (1983), the Festival of India in Britain (1982), and the Non-Aligned Movement Summit in New Delhi (1983). The production and reception of these spectacles is analysed against the context of the Emergency imposed by Mrs Gandhi in 1975. During this period, public opinion swayed against the incumbent Congress Party and Mrs Gandhi, who was consequently ousted in the 1977 elections. In certain ways, Mrs Gandhi’s ‘political resurrection’ in January 1980 reaffirmed her position as a popular national leader. However, she was conscious of the fragility of her dominance, and her dented image in public and the media. The primary objective of this thesis is to examine how Mrs Gandhi, through the visual medium of the ‘spectacle’, sought to remake her image from a ‘dictator’ of the Emergency days to a symbol of stability, aspirations, and national pride upon re-election. Additionally, it questions the success of this political project by turning its gaze toward the spectator-consumer – in this case a pre-liberalisation, urban middle class in India. Consulting a range of textual and visual archives, the thesis argues that the above ‘mega-media-events’ and their carefully constructed associations with consumption, leisure, and entertainment enabled Mrs Gandhi to secure legitimacy amongst established and emerging categories of the middle class in India. In doing so, it seeks to portray another dimension of Mrs Gandhi’s constructed image as a leader of this influential demographic in ‘the long 1980s’, a period which brought enduring shifts in the Indian socio-economic landscape a full decade before the era of liberalisation.